PENGARUH CORPORATE GOVERNANCE, LEVERAGE, UKURAN PERUSAHAAN, DAN SALES GROWTH TERHADAP PENGHINDARAN PAJAK - Lukitasari Winastuti, 11.05.52.0079; Hardiningsih, Pancawati (Students' Journal of Accounting and Banking, 2016)
This research aims to analyse the influence of corporate governance, leverage, the size of company, sales growth to tax avoidance to companies that in the list Corporate Governance Perception Index. The sample in this study of 59 companies a period of 2011-2013, the next few samples eliminated due to a problem of heteroskedastisitas, so the sample size to 57. Relation and (or) influence between variables is described by using multiple regression analysis. Based on the result showed that variables that effect negatively the size of company, and sales growth, while the possitive effect on the corporate governance, and leverage of tax avoidance.Keywords: Tax Avoidance, Corporate Governance, Leverage, Size Of The Company, Sales Growth